Strong non‐repudiation based on certificateless short signatures. Issue 3 (1st September 2013) - Chen, Yu‐Chi; Horng, Gwoboa; Liu, Chao‐Liang
Abstract : In this study, the authors consider certificateless signature (CLS) schemes for strong non‐repudiation. They show that previous security models which ensure that any user can have a unique key pair cannot guarantee a CLS scheme to achieve strong non‐repudiation. The authors then fix the security model and propose a new CLS scheme which provides strong non‐repudiation under the new model, assuming the computational Diffie–Hellman problem is intractable.